A comparative study of antinociceptive effect of fluoxetine with pentazocine in rodent model - H., Manjunatha C.; Ratnakar, Jagadishchandra S. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Chronic pain affects millions of people across the globe, commonly coexisting with depression. Antidepressants like fluoxetine have shown potential to have analgesic activity with superior safety profile and hence might be better suited in the treatment of chronic pain. The objective of this study was to evaluate the antinociceptive activity of fluoxetine and to compare the antinociceptive effect of fluoxetine with pentazocine. Methods: Adult albino rats weighing 150-200 grams were used in this study. Screening method used was Acetic acid induced writhing method in rats. Rats were divided into three groups of 5 animals and drugs administered as follows: group-1: distilled water (control), group-2: Fluoxetine, group-3: Pentazocine. All drugs were administered 30 minutes before the onset of pain stimulus. Statistical analysis was done by using one way-analysis of variance (one way ANOVA) followed by Tukey-Kramer test. Results: Fluoxetine failed to show significant antinociceptive activity in Acetic acid induced writhing method. Conclusions: Fluoxetine is an SSRI and one of the most commonly prescribed drug for depression. It is proven to act at multiple sites like serotonin transporter and opioid µ receptor, both of which may play a role in its analgesic activity.